Lipotoxic Effects of Gossypol Acetate Supplementation on Hepatopancreas Fat Accumulation and Fatty Acid Profile in Cyprinus carpio. (4th April 2022) - Zhang, Yuru; Zhang, Junmei; Ren, Yanhua; Zhang, Mengdan; Liang, Junping
Abstract : Cottonseed meal is an excellent protein source with low price and abundant nutrients, but the existence of free gossypol restricts its wide application in animal feeds. To explore the toxic effects of free gossypol, the effects of gossypol acetate on the growth performance, hepatopancreatic fat accumulation, and muscle fatty acid composition of the common carp ( Cyprinus carpio ) were investigated in the present study. Carp were randomly divided into four groups, which were fed a diet supplemented with 0, 170, 340, and 680 mg/kg gossypol acetate, respectively. After 60 days of feeding, the gossypol residue in the tissue, growth performance, blood biochemical indices, hepatopancreas histology, fatty acid components, and expression of key genes involved in lipid metabolism pathways were measured. It was found that the concentrations of free gossypol were increased significantly in the serum, bile, and hepatopancreas of carp fed 340 mg/kg and 680 mg/kg gossypol acetate (P < 0.05 ). Dietary gossypol acetate had a limited effect on growth performance, and high concentrations of gossypol acetate induced excessive hepatopancreatic fat deposition and hepatocyte injury in C. carpio . In addition, gossypol acetate decreased total polyunsaturated fatty acids (PUFAs) and docosahexaenoic acid in muscle. In the hepatopancreas, decreased HSL, PPARα, and CD36 may result in fat accumulation. In the muscle, decreased FADS2 may be the key reason for the decrease in PUFAs. Taken together, these findings indicated that dietary gossypol acetate can cause lipid metabolism disorders, such as hepatopancreatic damage and significant changes in tissue fatty acid profile, which are regulated by the key lipid metabolic genes in common carp.